Amplatzer PFO Occluder for treatment of incomplete LAA closure with AtriClip. (12th July 2021) - Gianni, Carola; Burkhardt, J. David; Della Rocca, Domenico G.; Natale, Andrea; Horton, Rodney P.
Abstract: Herein, we describe the use of an Amplatzer PFO Occluder to treat incomplete LAA closure due to a malpositioned AtriClip.